Studi Analisis Faktor Pengaruh Pertumbuhan Foreign Direct Investment di Indonesia Tahun 2010-2020 - Defrianto Wahyu Putra Pratama; Eni Setyowati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine how affecting economic risk, including the Bank Indonesia reference interest rate, loan-to-deposit ratio, GDP, currency rates, and the Corruption Perception Index (CPI), affects foreign direct investment (FDI) in Indonesia. The technique utilized is simultaneously and partially analyzed descriptive quantitative analysis. The method utilized in this study uses multiple linear regression to calculate the least squares approach of the OLS model (Ordinary Least Square) to look at the long-term and short-term situations of a country's plurality. It intends to identify the variables that affect the growth of FDI in Indonesia between 2010 and 2020 by using the ECM model (Error Correction Model) methodology.